Synaptic Conductances during Interictal Discharges in Pyramidal Neurons of Rat Entorhinal Cortex - Amakhin, Dmitry V.; Ergina, Julia L.; Chizhov, Anton V.; Zaitsev, Aleksey V. (Frontiers in Cellular Neuroscience, 2016)
In epilepsy, the balance of excitation and inhibition underlying the basis of neural network activity shifts, resulting in neuronal network hyperexcitability and recurrent seizure-associated discharges. Mechanisms involved in ictal and interictal events are not fully understood, in particular, because of controversial data regarding the dynamics of excitatory and inhibitory synaptic conductances. In the present study, we estimated AMPAR-, NMDAR-, and GABAAR-mediated conductances during two distinct types of interictal discharge (IID) in pyramidal neurons of rat entorhinal cortex in cortico-hippocampal slices. Repetitively emerging seizure-like events and IIDs were recorded in high extracellular potassium, 4-aminopyridine, and reduced magnesium-containing solution. An original procedure for estimating synaptic conductance during IIDs was based on the differences among the current-voltage characteristics of the synaptic components. The synaptic conductance dynamics obtained revealed that the first type of IID is determined by activity of GABAAR channels with depolarized reversal potential. The second type of IID is determined by the interplay between excitation and inhibition, with prominent early AMPAR and prolonged depolarized GABAAR and NMDAR-mediated components. The study then validated the contribution of these components to IIDs by intracellular pharmacological isolation. These data provide new insights into the mechanisms of seizures generation, development, and cessation.